The potential of agricultural biomass for adsorption of humic substances from tropical black water - Mohd Irwan Lu, Nurul Aida Lu (Universiti Malaysia Sarawak (UNIMAS), 2015)
The presence of humic substances in water affects the water quality as well as its treatability. They are removed using the conventional coagulation approach in the water treatment system. Adsorption using alternative adsorbents from agricultural wastes has received increasing attention due to their advantages of low cost, abundant availability and environmental friendly. To the best of our understanding, application of biosorbent for removal of humic substances from water remains scarce. Hence, in this study, we investigated the adsorption potential of various indigenous agriculture biomasses for removal of humic substances from peat swamp runoff. The adsorption isotherms were further evaluated using the standard humic acid. The adsorption potential of untreated biomass was less promising (< 45 %). With citric acid pretreatment, the adsorption capacity was significantly improved especially for groundnut shell, rice husk and sugarcane bagasse where the percentage removal attained were 63.81%, 58.70% and 57.48%, respectively. It was observed that various biomasses experienced delignification, dissolution and eventually chemical functionalization to different extents upon treatment. The isotherm models (Langmuir, Freundlich, Dubinin-Radushkevich and Temkin) showed that after treatment, the adsorption capacities was increased up to 4.99 mg/g, 3.93 mg/g and 18.98 mg/g for modified groundnut shell, rice husk and sugarcane bagasse, respectively.